Low-temperature conductive silver-copper paste and preparation method and application thereof
By using a low-temperature conductive silver-copper paste with a specific proportion of epoxy resin and acrylic resin in HJT batteries, the problem of insufficient wetting caused by the reduction of powder density of silver-copper paste is solved, and the printing properties and electrical properties are improved. It realizes efficient photoelectric conversion efficiency and reduces silver costs.
Patent Information
- Application Number
- CN202411619452.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-13
- Publication Date
- 2025-01-14
AI Technical Summary
In the production of HJT batteries, the specific surface area of the silver-clad copper slurry increases due to the decrease in powder density, resulting in insufficient surface wetting, and problems such as network blocking and grid breaking, virtual printing, low high-level ratio, and low current.
Low-temperature conductive silver-copper paste is used to combine epoxy resin and acrylic resin in a specific proportion to form organic separation between powder particles, improve the uniform dispersion and viscosity of powder particles, and combine moderate intramolecular force to solve printing and Electrical performance issues.
It achieves high aspect ratio, excellent electrical performance and environmental protection, reduces gate breakage and virtual printing, improves photoelectric conversion efficiency, is suitable for the production of HJT batteries, and reduces silver costs.
Smart Images

Figure SMS_1
Abstract
Description
Technical Field
[0001] The present application relates to the technical field of solar heterojunction cells, and in particular to a low-temperature conductive silver-copper paste and a preparation method and application thereof. Background Art
[0002] At present, my country's photovoltaic industry ranks among the world's top in terms of manufacturing scale, industrialization technology level, application market expansion, and industrial system construction. At present, it is in a critical period of transformation. PERC has faced the ceiling of improvement and is approaching the theoretical efficiency value. Transformation to new technologies is imminent. There are currently many new technology routes, such as Topcon, HJT, BC, and perovskite. Among them, Topcon is the choice of many old crystalline silicon battery factories because of its relatively mature route and low transformation cost. It can be directly transformed from PERC to Topcon production line, but it also faces many problems, such as high attenuation, high silver consumption, and it is difficult to improve efficiency. It requires iterative technology to add equipment, and there are many processes with low yield; BC and perovskite are currently immature technologies, and the yield, range efficiency and reliability all need to be verified. HJT technology is the first choice for many new cross-border photovoltaic companies. Although the investment in new production lines is large, there are fewer subsequent production processes and it makes up for many shortcomings of Topcon. It has many advantages such as high opening voltage, low temperature coefficient, no LID, no LeTID (photothermal attenuation), no PID (potential induced attenuation), symmetrical structure, easy thinning, fewer processes, high yield and low energy consumption.
[0003] In 1974, Walther Fuhs of the University of Marburg in Germany first proposed the HJT structure, and in 1983 he successfully developed an HJT cell (heterojunction cell) with a conversion efficiency of 12.3%. Between 1991 and 1996, Japan's Sanyo Company introduced intrinsic amorphous silicon into the heterojunction cell structure, achieving a significant improvement in conversion efficiency. In 2017, Japan's Kaneka combined back contact technology with HJT to achieve a world record of 26.6% cell conversion efficiency. As the mass production process matured, manufacturers from various countries began to invest in HJT production lines, from the initial pilot line to the 100MW mass production line, and then to the GW mass production line. HJT cells have been applied on a large scale.
[0004] The structure and principle of HJT battery is to form a heterojunction on an N-type crystalline silicon substrate by depositing amorphous silicon as a passivation layer. The open circuit voltage of the battery with this structure is higher and the efficiency is relatively high. At the same time, the outermost layer has a TCO transparent conductive layer. The HJT battery process uses a low-temperature process. The temperature of the silver paste is usually around 200°C, which is convenient for using thinner N-type silicon wafers, so that there is a large space for reducing silicon wafer costs in the future. The metallized grid line is superimposed with 0BB technology (no main grid technology) and silver-clad copper technology, which directly reduces the non-silicon cost and approaches the non-silicon cost of PERC and Topcon. At present, the mass production efficiency of the HJT battery industry is about 26%, the bifacial rate is more than 90%, and the yield is more than 99%. It is also the best solution for superimposing on the next generation of high-efficiency solar cell perovskite, because after superposition, the light segment is not repeatedly absorbed, which can maximize the use of sunlight. At present, the efficiency of superimposed perovskite batteries has reached 33.7%. The later development will definitely be PERC, topcon, and HJT. Therefore, HJT technology is expected to become the mainstream technology of the next generation of superimposed perovskite.
[0005] However, the current price per watt continues to decline, while the price of silver powder continues to rise, which brings tremendous pressure to the HJT battery production stage. The use of silver-coated copper slurry can solve the cost reduction problem, but the silver-coated copper slurry on the market currently has the problem of increased specific surface area due to the reduction of powder density, which in turn leads to insufficient surface wetting, and is prone to problems such as slurry blocking the grid, broken grid, virtual printing, low aspect ratio, and low current. Summary of the invention
[0006] In order to address the deficiencies in the prior art, the present application provides a low-temperature conductive silver-copper paste that can be used for HJT batteries. The paste has excellent printability, higher conversion efficiency brought about by an excellent aspect ratio, and good environmental performance. It can effectively solve the problem of increased specific surface area due to reduced powder density in the current silver-clad copper paste on the market, which in turn leads to insufficient surface wetting, and is prone to problems such as slurry blocking the mesh, broken grid, virtual printing, low aspect ratio, and low current.
[0007] To this end, the first aspect of the present application provides a low-temperature conductive silver-copper paste, which comprises the following components in parts by weight: Silver powder 1~96 parts; Silver-coated copper powder 1-96 parts; Resin 0.1~5 parts; Curing agent 0.1~5 parts; 1-10 parts of organic solvent; Wherein, the resin includes epoxy resin and acrylic resin, and the mass ratio of epoxy resin to acrylic resin is 1:(0.1~1.6).
[0008] The components of the low-temperature conductive silver-copper paste in this application are not randomly superimposed. Each component has a different role. The particle sizes of silver powder and silver-coated copper powder cooperate with each other, and the resin and organic solvent cooperate with each other and match the appropriate curing agent according to the selected resin. The combination of silver powder and silver-coated copper powder determines the conductivity and affects the electrical properties. At the same time, the surface shape and specific surface area of the two powders affect the printability; the combination of resin and organic solvent determines the printing performance, but also affects the shrinkage of the powder (silver powder and silver-coated copper powder) after curing, thereby affecting the contact between the powders and ultimately affecting the electrical properties; the curing agent affects the curing rate of the resin. Different curing agents have different curing rates in the same process time, resulting in different curing degrees, affecting the contact of the powder, thereby greatly affecting the electrical properties. At the same time, the matching degree with the resin is different due to the different curing agents added, which in turn affects the printing performance. Therefore, each component in the low-temperature conductive silver-copper paste has different focuses, and one hair moves the whole body.
[0009] Furthermore, the low-temperature conductive silver-copper paste of the present application can effectively solve the problems of insufficient surface wetting caused by the increase in specific surface area due to the reduced powder density of the silver-coated copper paste on the market, and the paste is prone to problems such as grid blocking, broken grid, virtual printing, low aspect ratio, and low current. The specific reasons are as follows: The resin of the present application is matched with epoxy resin and acrylic resin in a specific content, and is wetted with acrylic resin, and then linked by epoxy resin to form an organic phase separation between powder particles, which is not easy to cause large particle agglomeration, effectively reducing the risk of broken grid, and the resin can make the powder particles evenly dispersed after being coated on the surface of the powder particles, and the resin and powder particles will not separate in the long-term printing, and the slurry will not dry out in the later stage, which will lead to the increase of slurry viscosity on the screen, poor mesh passing, and finally lead to broken grid and virtual printing problems. At the same time, the low-temperature conductive slurry of the present application is reasonably matched with epoxy resin and acrylic resin, and the slurry viscosity is moderate, the powder particles have high sphericity and moderate intramolecular force, and the powder particles will not be too large due to excessive intramolecular force, resulting in blockage, poor mesh passing, and difficulty in stacking. It will not cause linear collapse, too wide line width, low line height, low aspect ratio, and low current due to insufficient intermolecular pulling force caused by too low intramolecular force. Therefore, the low-temperature conductive silver-copper paste provided in this application can solve the above-mentioned printing and efficiency problems encountered by the current HJT low-temperature conductive paste through the reasonable combination of resins, and can achieve long-term excellent printing with high efficiency. Moreover, with the continuous release of HJT production capacity and the subsequent stable advancement of HJT superimposed perovskite, the low-temperature conductive silver-copper paste of this application has a broad market and development space.
[0010] The low-temperature conductive silver-copper paste provided in this application is covered on the surface of the ITO layer of the HJT battery by screen printing of a specific pattern, and has good contact with the ITO layer, and then heat-cured by 200°C hot air or infrared to form fine grid lines. The low-temperature conductive silver-copper paste provided in this application has been verified by the production line to have: excellent printability, high aspect ratio, excellent electrical properties and good environmental protection.
[0011] In the present application, the number average molecular weight of the epoxy resin used may be between 5 and 10,000.
[0012] In some specific embodiments, the mass ratio of the epoxy resin to the acrylic resin can be 1:0.1, 1:0.4, 1:0.6, 1:0.7, 1:1.0, 1:1.3 or 1:1.6, etc.
[0013] In some preferred embodiments, the mass ratio of the epoxy resin to the acrylic resin is 1:(0.4-1.3); in some further preferred embodiments, the mass ratio of the epoxy resin to the acrylic resin is 1:(0.6-1.0).
[0014] The present application helps to improve the printing performance and electrical properties of the prepared low-temperature conductive silver-copper paste by controlling the mass ratio of epoxy resin to acrylic resin within the above range.
[0015] In some embodiments, the epoxy resin is selected from at least one of alicyclic epoxy resins, linear aliphatic epoxy resins, glycidyl ether epoxy resins, glycidyl ester epoxy resins, and glycidyl amine epoxy resins.
[0016] In some specific embodiments, the epoxy resin is at least one selected from bisphenol A epoxy resin, bisphenol F epoxy resin, tetraphenol ethane tetraglycidyl ether epoxy resin, resorcinol bisglycidyl ether epoxy resin and pyrogallol triglycidyl ether epoxy resin.
[0017] In some preferred embodiments, the epoxy resin is bisphenol A epoxy resin, pyrogallol triglycidyl ether epoxy resin and tetraphenol ethane tetraglycidyl ether epoxy resin, and the mass ratio of bisphenol A epoxy resin, pyrogallol triglycidyl ether epoxy resin and tetraphenol ethane tetraglycidyl ether epoxy resin in the mixture is 1:1:1.
[0018] The inventors of the present application creatively discovered through research that by reasonably combining the above-mentioned specific contents of bisphenol A epoxy resin, pyrogallol triglycidyl ether and tetraphenolethane tetraglycidyl ether epoxy resin, the powder particles after the epoxy resin wets the acrylic resin can be better linked, thereby improving the printing performance and electrical properties of the obtained low-temperature conductive silver-copper paste.
[0019] In some embodiments, the acrylic resin is a thermoplastic acrylic resin.
[0020] In the present application, the thermoplastic acrylic resin used is a low molecular weight thermoplastic acrylic resin, and the number average molecular weight of the low molecular weight thermoplastic acrylic resin is between 2 and 5000, for example, the thermoplastic acrylic resin LR-7622.
[0021] In some embodiments, the D50 particle size of the silver powder and the silver-coated copper powder is independently 0.1-10 μm, preferably 1-8 μm; the D97 particle size of the silver powder and the silver-coated copper powder is independently 1-12 μm, preferably 6-10 μm.
[0022] In some embodiments, the specific surface area of the silver powder and the silver-coated copper powder is less than 2 m 2 / g, wherein the silver-coated copper powder is preferably less than 0.8m 2 / g, silver powder is preferably less than 1.8m 2 / g; the tap density of the silver powder and the silver-coated copper powder is independently 2 to 10 g / cm 3 , preferably 5~7.5g / cm 3 .
[0023] The present application uses a combination of silver powder and silver-coated copper powder having the above parameters and a suitable resin to make the prepared low-temperature conductive silver-copper paste have better printing performance.
[0024] In some embodiments, the mass fraction of silver in the silver-coated copper powder is 10-30%.
[0025] In the present application, the silver-coated copper powder is used to replace part of the pure silver powder for the preparation of low-temperature conductive paste, which greatly reduces the paste cost. At the same time, through the reasonable combination of resins, the problem of the silver-coated copper paste on the market currently increasing the specific surface area due to the reduction in powder density is solved, which leads to insufficient surface wetting, and is prone to problems such as slurry blocking the grid, broken grid, virtual printing, low aspect ratio, and low current.
[0026] In some embodiments, the curing agent is selected from at least one of polythiol, aliphatic polyamine, aromatic polyamine, diethylaminopropylamine, imidazole, tertiary amine salt, alicyclic amine, dicyandiamide, isocyanate, imidazole derivatives, aromatic polyamine and acid anhydride; the organic solvent is selected from at least one of terpineol, propylene glycol methyl ether acetate, cyclohexanone, xylene, dodecanol ester, triethylene glycol butyl ether, anisole, isopropanol, ethylene glycol phenyl ether, diethylene glycol butyl ether, butyl carbitol acetate, butyl carbitol and propylene glycol monobutyl ether.
[0027] The second aspect of the present application provides a method for preparing a low-temperature conductive silver-copper paste as described in the first aspect of the present application, the method comprising: mixing silver powder, silver-coated copper powder, resin, organic solvent and curing agent to obtain a mixture; rolling and dispersing the mixture to obtain the low-temperature conductive silver-copper paste.
[0028] In the present application, a three-roll mill can be used to roll the mixture, and the number of rolling can be 2 to 8 times. The viscosity of the prepared low-temperature conductive silver-copper paste is 30 to 150 Pa.s (Viscosity using a Brookfield model DVNXHBCBG Rheometer with spindle CPE-51 @ 25°C), the fineness is less than 7 μm, and the solid content is 90 to 95 wt%.
[0029] In the present application, the preparation method of the low-temperature conductive silver-copper paste is simple to operate, has no special requirements on equipment, and is easy to industrialize.
[0030] The third aspect of the present application provides an HJT battery, wherein the electrode grid lines in the HJT battery are printed using the low-temperature conductive silver-copper paste as described in the first aspect of the present application or the low-temperature conductive silver-copper paste prepared by the method described in the second aspect.
[0031] When the low-temperature conductive silver-copper paste of the present application is used for silk screen or full-open alloy screen printing, it is easier to pass through the screen, so that the broken grid and virtual printing phenomena are reduced; at the same time, the prepared grid line has a higher aspect ratio, which reduces the shading area of the electrode line and improves the current and photoelectric conversion efficiency of the HJT battery.
[0032] The beneficial technical effects of the present application are as follows: the low-temperature conductive silver-copper paste provided by the present application can effectively increase the surface wetting of powder particles, improve the wettability of the slurry, and ensure long-term printability through the reasonable combination of resins. While enhancing printability, it has excellent double-sidedness, excellent reliability, excellent aspect ratio, and excellent photoelectric conversion efficiency. The overall performance of the production line verification is excellent, which solves the problems of broken grids, virtual printing, linear collapse, excessive line width, low line height, low aspect ratio, and low current resulting from poor printability on the current production line. At the same time, the preparation method of the low-temperature conductive silver-copper paste is simple to operate, has no special requirements for equipment, is easy to industrialize, and has broad application prospects. DETAILED DESCRIPTION
[0033] In order to make the present application easier to understand, the present application will be further described in detail below in conjunction with the examples, which are merely illustrative and are not intended to limit the scope of application of the present application. The raw materials or components used in the present application can be obtained through commercial routes or conventional methods unless otherwise specified.
[0034] Example 1: Preparation of low-temperature conductive silver-copper paste Raw material composition: 19 parts of silver powder, 75 parts of silver-coated copper powder, 4 parts of resin, 1 part of curing agent, and 1 part of organic solvent; the D50 particle size of the silver powder and the silver-coated copper powder is 5μm, the D97 particle size is 8μm, and the specific surface area of the silver-coated copper powder is less than 0.8m 2 / g, the specific surface area of silver powder is less than 1.8m 2 / g, the tap density of silver-coated copper powder and silver powder is 6.0g / cm 3 The mass fraction of silver in the silver-coated copper powder is 15%; the resin is a mixture of epoxy resin and acrylic resin, and the mass ratio of epoxy resin to acrylic resin in the mixture is 1:0.1, the epoxy resin is bisphenol A epoxy resin (number average molecular weight is 8000), and the acrylic resin is a thermoplastic acrylic resin (such as LR-7622); the curing agent is an imidazole derivative (dimethylimidazole); the organic solvent is a mixture of triethylene glycol butyl ether, butyl carbitol acetate, dodecyl alcohol ester and ethylene glycol phenyl ether, and the volume ratio of triethylene glycol butyl ether, butyl carbitol acetate, dodecyl alcohol ester and ethylene glycol phenyl ether in the mixture is 1:1:1:1.
[0035] Preparation process: Add the above silver powder, silver-coated copper powder, resin, organic solvent and curing agent into a double planetary mixer, stir and mix for 3 hours to obtain a mixture; put the mixture into a three-roll mill for rolling 5 times, disperse and stir for 3 hours to obtain a low-temperature conductive silver-copper paste. The fineness of the obtained low-temperature conductive silver-copper paste is less than 7μm, and the solid content is 94wt%.
[0036] Example 2: Preparation of low-temperature conductive silver-copper paste Raw material composition: basically the same as Example 1, except that the mass ratio of epoxy resin to acrylic resin is 1:0.4.
[0037] Preparation process: Same as Example 1.
[0038] Example 3: Preparation of low-temperature conductive silver-copper paste Raw material composition: basically the same as Example 1, except that the mass ratio of epoxy resin to acrylic resin is 1:0.7.
[0039] Preparation process: Same as Example 1.
[0040] Example 4: Preparation of low-temperature conductive silver-copper paste Raw material composition: basically the same as Example 1, except that the mass ratio of epoxy resin to acrylic resin is 1:1.
[0041] Preparation process: Same as Example 1.
[0042] Example 5: Preparation of low-temperature conductive silver-copper paste Raw material composition: basically the same as Example 1, except that the mass ratio of epoxy resin to acrylic resin is 1:1.3.
[0043] Preparation process: Same as Example 1.
[0044] Example 6: Preparation of low-temperature conductive silver-copper paste Raw material composition: basically the same as Example 1, except that the mass ratio of epoxy resin to acrylic resin is 1:1.6.
[0045] Preparation process: Same as Example 1.
[0046] Example 7: Preparation of low-temperature conductive silver-copper paste Raw material composition: basically the same as Example 3, except that there are 9 parts of silver powder and 85 parts of silver-coated copper powder.
[0047] Preparation process: Same as Example 1.
[0048] Example 8: Preparation of low-temperature conductive silver-copper paste Raw material composition: basically the same as Example 3, except that there are 45 parts of silver powder and 49 parts of silver-coated copper powder.
[0049] Preparation process: Same as Example 1.
[0050] Example 9: Preparation of low-temperature conductive silver-copper paste Raw material composition: basically the same as Example 3, except that the ratio of bisphenol A epoxy resin, pyrogallol triglycidyl ether epoxy resin, and tetraphenolethane tetraglycidyl ether epoxy resin in the epoxy resin mixture is 1:1:1.
[0051] Preparation process: Same as Example 1.
[0052] Example 10: Preparation of low-temperature conductive silver-copper paste Raw material composition: basically the same as Example 9, except that the mass ratio of epoxy resin mixture to acrylic resin is 1:0.6.
[0053] Preparation process: Same as Example 1.
[0054] Comparative Example 1: Preparation of low-temperature conductive silver-copper paste Raw material composition: basically the same as Example 1, except that the resin in the raw material is only epoxy resin.
[0055] Preparation process: Same as Example 1.
[0056] Comparative Example 2: Preparation of low-temperature conductive silver-copper paste Raw material composition: basically the same as Example 1, except that the mass ratio of epoxy resin to acrylic resin in the resin mixture in the raw materials is 1:2.
[0057] Preparation process: Same as Example 1.
[0058] Test Example 1 The viscosity of the low-temperature conductive silver-copper paste prepared in Examples 1-10 and Comparative Examples 1-2 was tested (Viscosity using a Brookfield model DVNXHBCBG Rheometer with spindle CPE-51 @ 25°C), and then the low-temperature conductive silver-copper paste prepared in Examples 1-10 and Comparative Examples 1-3 was used to cover the surface of the ITO layer of the HJT battery by screen printing, and then thermally cured by 200°C high-temperature hot air to form fine grid lines, thereby obtaining HJT battery cells printed with grid lines. A 3D optical microscope was used to measure the line height and line width of the grid lines, and the number of broken grids and the number of coarse grids were observed; a Halm tester was used to test the photoelectric conversion efficiency Eta (%) of the HJT battery cells prepared by each low-temperature conductive silver-copper paste under standard test conditions (STC). The test results are shown in Table 1.
[0059] Table 1: Performance parameter test results of HJT cells
[0060] From the above test results, it can be seen that compared with the low-temperature conductive silver-copper paste prepared in Comparative Examples 1 and 2, the HJT battery with electrode grid lines prepared by screen printing the low-temperature conductive silver-copper paste prepared in Examples 1-10 has better photoelectric conversion efficiency.
[0061] Specifically, from the test results of Examples 1-6 and Comparative Examples 1-2, it can be seen that when the resin in the low-temperature conductive silver-copper paste is a mixture of epoxy resin and acrylic resin, it is helpful to improve the printing and electrical properties of the low-temperature conductive silver-copper paste. At the same time, when the mass ratio of epoxy resin to acrylic resin is controlled at 1: (0.4~1.3), the printing and electrical properties of the low-temperature conductive silver-copper paste can be better, and the most preferred mass ratio is 1: 0.7. From the test results of Examples 3 and Examples 7 and 8, it can be seen that when the silver powder content in the low-temperature conductive silver-copper paste is in the range of 20~50%, the printing performance of the slurry prepared using the same organic solvent is good. The slurry of Example 3 has a wide applicability, which can match the current market demand for reducing the limit of silver content and take into account the high filling demand brought by the high silver content. From the test results of Examples 3 and 9 and 10, it can be seen that when the epoxy resin mixture is changed into bisphenol A epoxy resin, pyrogallol triglycidyl ether epoxy resin, and tetraphenol ethane tetraglycidyl ether epoxy resin (ratio 1:1:1) at the same time, the electrical performance is better, but the proportion of acrylic resin needs to be fine-tuned, which can make the printability and electrical properties of the low-temperature conductive silver-copper paste better.
[0062] It should be noted that the embodiments described above are only used to explain the present application and do not constitute any limitation to the present application. The present application is described with reference to typical embodiments, but it should be understood that the words used therein are descriptive and explanatory words, rather than restrictive words. The present application may be modified as specified within the scope of the claims of the present application, and the present invention may be revised without departing from the scope and spirit of the present application. Although the present application described therein relates to specific methods, materials and embodiments, it does not mean that the present application is limited to the specific examples disclosed therein. On the contrary, the present application can be extended to all other methods and applications with the same functions.
Claims
1. A low-temperature conductive silver-copper paste, characterized in that: The low-temperature conductive silver-copper paste comprises the following components in parts by weight: Silver powder 1~96 parts; Silver-coated copper powder 1-96 parts; Resin 0.1~5 parts; Curing agent 0.1~5 parts; 1-10 parts of organic solvent; Wherein, the resin includes epoxy resin and acrylic resin, and the mass ratio of epoxy resin to acrylic resin is 1:(0.1-1.6); preferably 1:(0.4-1.3).
2. The low-temperature conductive silver-copper paste according to claim 1, characterized in that: The epoxy resin is selected from at least one of alicyclic epoxy resins, linear aliphatic epoxy resins, glycidyl ether epoxy resins, glycidyl ester epoxy resins and glycidyl amine epoxy resins.
3. The low-temperature conductive silver-copper paste according to claim 2, characterized in that: The epoxy resin is at least one selected from bisphenol A epoxy resin, bisphenol F epoxy resin, tetraphenol ethane tetraglycidyl ether epoxy resin, resorcinol bisglycidyl ether epoxy resin and pyrogallol triglycidyl ether epoxy resin.
4. The low-temperature conductive silver-copper paste according to any one of claims 1 to 3, characterized in that: The acrylic resin is a thermoplastic acrylic resin.
5. The low-temperature conductive silver-copper paste according to any one of claims 1 to 3, characterized in that: The D50 particle size of the silver powder and the silver-coated copper powder is independently 0.1-10 μm, preferably 1-8 μm; the D97 particle size of the silver powder and the silver-coated copper powder is independently 1-12 μm, preferably 6-10 μm.
6. The low-temperature conductive silver-copper paste according to any one of claims 1 to 3, characterized in that: The specific surface area of the silver powder and the silver-coated copper powder is less than 2m 2 / g, wherein the silver-coated copper powder is preferably less than 0.8m 2 / g, silver powder is preferably less than 1.8m 2 / g; the tap density of the silver powder and the silver-coated copper powder is independently 2 to 10 g / cm 3 , preferably 5~7.5g / cm 3 .
7. The low-temperature conductive silver-copper paste according to any one of claims 1 to 3, characterized in that: The mass fraction of silver in the silver-coated copper powder is 10-30%.
8. The low-temperature conductive silver-copper paste according to any one of claims 1 to 3, characterized in that: The curing agent is selected from at least one of polythiol, aliphatic polyamine, aromatic polyamine, diethylaminopropylamine, imidazole, tertiary amine salt, alicyclic amine, dicyandiamide, isocyanate, imidazole derivatives, aromatic polyamine and acid anhydride; the organic solvent is selected from at least one of terpineol, propylene glycol methyl ether acetate, cyclohexanone, xylene, dodecanol ester, triethylene glycol butyl ether, anisole, isopropanol, ethylene glycol phenyl ether, diethylene glycol butyl ether, butyl carbitol acetate, butyl carbitol and propylene glycol monobutyl ether.
9. A method for preparing a low-temperature conductive silver-copper paste as claimed in any one of claims 1 to 8, characterized in that: The method comprises: mixing silver powder, silver-coated copper powder, resin, organic solvent and curing agent to obtain a mixture; rolling and dispersing the mixture to obtain the low-temperature conductive silver-copper paste.
10. A HJT battery, characterized in that: The electrode grid lines in the HJT battery are printed using the low-temperature conductive silver-copper paste described in any one of claims 1 to 8 or the low-temperature conductive silver-copper paste prepared by the method described in claim 9.
Citation Information
Patent Citations
Silver-coated copper silver paste and preparation method thereof
CN115188519A
Conductive adhesive and preparation method thereof
CN117987054A
Low-temperature sintered silver paste with high sintering activity and preparation method thereof
CN118658656A
Cited By
Low-silver conductive paste for back contact battery as well as preparation method and application of low-silver conductive paste
CN120148932A
Silver-coated copper conductive low-temperature slurry and preparation method and application thereof
CN120413132A